Internet information agents: a collaboration model for e-commerce applications - Yeo, Heng Ngi. (2008)
The aim of this report is to provide an account of the research work accomplished. It presents the retionale for employing mobile agents in supporting Internet business collaboration, the choice of mobile agent tools, and the design of a generic agent collaboration model, including the roles of XML in the proposed model.